Unlocking antagonistic potential of Bacillus amyloliquefaciens KRS005 to control gray mold - Qi, Hong-Yue; Wang, Dan; Han, Dongfei; Song, Jian; Ali, Muhammad; Dai, Xiao-Feng; Zhang, Xiao-Jun; Chen, Jie-Yin (Frontiers in Microbiology, 2023)
To establish a safe, efficient, and simple biocontrol measure for grey mold disease caused by Botrytis cinerea, the basic characteristics and antifungal activity of KRS005 were studied from multiple aspects including morphological observation, multilocus sequence analysis and typing (MLSA - MLST), physical-biochemical assays, broad-spectrum inhibitory activities, control efficiency of gray mold, and determination of plant immunity. The strain KRS005, identified as Bacillus amyloliquefaciens, demonstrated broad-spectrum inhibitory activities against various pathogenic fungi by dual confrontation culture assays, of which the inhibition rate of B. cinerea was up to 90.3%. Notably, through the evaluation of control efficiency, it was found that KRS005 fermentation broth could effectively control the occurrence of tobacco leaves grey mold by determining the lesion diameter and biomass of B. cinerea on tobacco leaves still had a high control effect after dilution of 100 folds. Meanwhile, KRS005 fermentation broth had no impact on the mesophyll tissue of tobacco leaves. Further studies showed that plant defense-related genes involved in reactive oxygen species (ROS), salicylic acid (SA), and jasmonic acid (JA)-related signal pathways were significantly upregulated when tobacco leaves were sprayed with KRS005 cell-free supernatant. In addition, KRS005 could inhibit cell membrane damage and increase the permeability of B. cinerea. Overall, KRS005, as a promising biocontrol agent, would likely serve as an alternative to chemical fungicides to control gray mold.